PENGARUH STRUKTUR ASET, TINGKAT PERTUMBUHAN PENJUALAN, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL - Nataliana Bebasari; Erin Soleha (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of asset structure, sales growth rate, and profitability on the capital structure of PT Unilever Indonesia Tbk., which was listed on the Indonesia Stock Exchange for the period 2011-2021. The population in this study was the financial statements of PT Unilever Indonesia Tbk. The sample in this study included financial statements of the company published from 2011 up to 2021. The highest capital structure will occur in 2021, reaching 49%. This shows that the total liability of PT Uniler Indonesia Tbk is 0.49 times greater than its total equity, which means that the company's total debt guaranteed by its own capital is Rp. 0.49. Meanwhile, the lowest capital structure occurred in 2011 at 7%. This shows that the total liability of PT Unilever Indonesia Tbk is 0.07 times greater than its total equity, which means that the total debt guaranteed by the company's own capital is Rp. 0.07. So it can be concluded that the capital structure of PT Unilever Indonesia Tbk for the 2011-2021 period has fluctuated. Based on the results of the partial study or t test, the asset structure variable partially had no significant effect on capital structure, the sales growth rate variable partially had a negative and significant effect on capital structure, and profitability partially has no significant effect on capital structure.